Ação da azitromicina em vilos placentários humanos infectados por Toxoplasma gondii: um modelo experimental de tratamento da toxoplasmose congênita - Filice, Letícia de Souza Castro (2013)
Toxoplasmosis is a worldwide zoonosis, caused by the protozoan Toxoplasma gondii. Although it is an usuall asymptomatic infection, the toxoplasmosis can manifest as a potentially serious disease in immunocompromised individuals and when acquired during pregnancy. The treatment of toxoplasmosis during pregnancy when the fetal infection is confirmed is based in the association of pyrimethamine, sulfadiazine and folinic acid (PSA). Pyrimethamine is potentially toxic and should not be used in the first trimester of pregnancy. The azalide antibiotic azithromycin presents efficacy in a wide range of bacterial infections and antimalarial activity, and it is considered safe for use during pregnancy. The objective of the present study was to evaluate the efficacy of azithromycin in controlling T. gondii infection in human placentas from third trimester. The placental villi were infected or not with tachyzoites of T. gondii and treated with various concentrations of azithromycin or PSA. The villous placenta were processed for morphological analysis, T. gondii intracellular proliferation and immunohistochemistry; and supernatants were evaluated for measuring the activity of LDH, cytokine, hormone production and nitrite. In non-cytotoxic doses (200 and 1000 ug/ml), treatment with azithromycin or PSA did not alter the morphology of the placental villi. Both antibiotics were able to reduce significantly the T. gondii intracellular proliferation, and the treatment with PSA promoted increase of IL-12 and IL-10 reduce, whereas azithromycin induced an increase in IL-2 and IL-6 in the groups infected with T. gondii, and reduced production of estradiol, progesterone and hCG. Moreover, the previous treatment of T. gondii with antibiotics was able to control the replication of the parasite, showing direct action of drugs on T. gondii. Thus, our data suggest that azithromycin, as PSA, was able to control the infection with T. gondii in an experimental model of human placental explants of third trimester. Additionally our data suggest that azithromycin may be an alternative selection for treatment of congenital toxoplasmosis, expanding the therapeutic strategies to control the parasite in maternal fetal interface.